Aging does not compromise in vitro oscillation of the suprachiasmatic nuclei but makes it more vulnerable to constant light - Polidarová, Lenka; Sládek, Martin; Novosadová, Zuzana; Sumová, Alena (Chronobiology international, 2017)
Circadian regulation of behavior worsens with age, however, the mechanism behind this phenomenon is still poorly understood. Specifically, it is not clear to what extend the ability of the circadian clock in the suprachiasmatic nuclei (SCN) to generate the rhythm is affected by aging. This study aimed to ascertain the effect of aging on the functioning of the SCN of mPer2Luciferase mice under unnatural lighting conditions, such as constant light (LL). Under LL, which worsened the age-induced effect on behavioral rhythms, a marginal age-dependent effect on in vitro rhythmicity in explants containing the middle, but not the rostral/caudal, regions of the SCN was apparent; the proportion of mice in which middle-region SCN explants were completely arrhythmic or had an extremely long period (>30 h) was 47% in aged mice and 27% in adults. The results suggest that in some of the aged animals, LL may weaken the coupling among oscillators in specific sub-regions of the SCN, leaving other sub-regions better synchronized. In the standard light/dark cycle and in constant darkness, the SCN ability to produce bioluminescence rhythms in vitro was not compromised in aged mice although aging significantly affected their SCN-driven locomotor activity rhythms. Therefore, our results demonstrate that although age worsened the SCN output rhythm, the SCN molecular core clock mechanism itself was relatively resilient to aging in these same animals. The results suggest the involvement of pathways downstream of the core clock mechanism which are responsible for this phenomenon.
Keywords: myši; cirkadiánní proteiny Period; Gene Expression Regulation; Aging; Mice, Knockout; luciferasy; Male; myši knockoutované; Circadian Rhythm; chování zvířat; Light; stárnutí; Luciferases; Photoperiod; Mice; pohybová aktivita; Animals; světlo; mPer2Luc mice; zvířata; constant light; cirkadiánní rytmus; mužské pohlaví; nucleus suprachiasmaticus; regulace genové exprese; fotoperioda; Behavior, Animal; ženské pohlaví; Motor Activity; Female; Period Circadian Proteins; circadian clock; Suprachiasmatic Nucleus; suprachiasmatic nuclei